A method for producing hydrogen from biomass
By combining a multi-metal magnetic porous catalyst with a depolymerization pretreated active liquid, the problem of many by-products and low conversion of hydrogen in the production of hydrogen by biomass is solved, efficient and clean hydrogen production is achieved, and the production cost of catalysts is reduced.
Patent Information
- Application Number
- CN202410712328.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-06-04
Smart Images

Figure CN118703233B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomass utilization, and in particular to a method for producing hydrogen from biomass. Background Art
[0002] Hydrogen is non-toxic, light, and has good combustion properties. It has the highest calorific value among traditional fuels and is recognized as a clean energy source. Its efficient development and utilization will help solve the energy crisis and environmental pollution problems. At present, hydrogen production basically relies on fossil energy, which makes hydrogen energy unable to achieve the renewable and clean process of the whole process. Biomass is valued for its zero carbon dioxide emissions and renewable resources. The energy utilization of biomass can effectively alleviate the depletion of fossil energy and the ecological and environmental problems it brings, and is an important path to achieve sustainable development. According to statistics, the annual biomass production in the world is about 30 billion tons, but only 4wt% is used as energy, and there is huge potential for hydrogen production. Biomass hydrogen production mainly includes biological method and thermochemical conversion method. From the application point of view, the biological method of hydrogen production technology is not mature enough, the reaction rate is low, and it is not easy to scale up. The technical route of hydrogen production by catalytic reforming of biomass liquid products is complicated, while the thermochemical method of hydrogen production is easier to achieve large-scale production and therefore attracts more attention.
[0003] The complex and robust structure of biomass makes it difficult to produce hydrogen directly. Currently, hydrogen is mainly produced by pyrolysis, which requires harsh conditions such as high temperature and high pressure. The side reactions and incomplete conversion during the reaction process result in low biomass utilization and low hydrogen yield. Therefore, the method of producing hydrogen from biomass using thermochemical conversion technology is currently a technology that has attracted much attention. Since the biomass catalytic thermal conversion process is simple, hydrogen-rich gas can be prepared in a targeted manner by adjusting the working conditions. However, the biomass composition is complex and has a high oxygen content, and there are many thermal conversion reaction pathways, resulting in problems such as wide distribution of products and low hydrogen conversion rate. How to select a catalyst that can effectively promote the directional conversion of biomass depolymerization into organic small molecule products, and improve the yield and selectivity of hydrogen, and improve the thermal conversion efficiency, is a difficult problem that needs to be solved urgently.
[0004] Biomass depolymerization, which has been widely studied in the prior art, usually requires the use of precious metal catalysts, and exogenous hydrogen needs to be added during the depolymerization process. The depolymerization reaction mechanism is complex, the reaction conditions during the depolymerization process are harsh, the depolymerization product selectivity is poor, the products are complex, the separation and purification of the products are relatively difficult, and the depolymerization efficiency is low. These are all problems currently faced by biomass for hydrogen production.
[0005] A Chinese patent with announcement number CN105692551B discloses a method and device for efficiently producing hydrogen-rich gas from biomass, wherein biomass and water vapor are continuously fed into a fluidized bed reactor for rapid cracking at 600°C, and the generated cracking gas and biochar are fed into an entrained bed reactor together with water vapor for synchronous gasification of the cracking gas and biochar, and the gas coming out of the entrained bed reactor is subjected to catalytic reforming reaction to generate hydrogen-rich gas, and the catalytic reforming uses Co and Cu-based modified catalysts, and there are problems such as cumbersome and complicated biomass water vapor gasification reaction process, high reaction temperature, and low hydrogen yield.
[0006] A Chinese patent with publication number CN116064169A discloses a method and system for producing hydrogen from biomass, which adopts a new thermochemical conversion hydrogen production process and simplifies the hydrogen production process. However, this method also produces hydrogen through high-temperature carbonization. This method has many by-products, such as activated carbon and tar, which is not conducive to the production of hydrogen.
[0007] Therefore, how to reduce by-products in the process of biomass thermal conversion to hydrogen production, depolymerize biomass into small organic molecules, and further improve the hydrogen conversion rate is a current problem. Summary of the invention
[0008] In order to solve the above problems, the purpose of the present invention is to provide a method for efficiently producing hydrogen from biomass using a thermal catalytic system to solve one or more technical problems existing in the prior art and at least provide a beneficial option or create conditions.
[0009] The main body of biomass is lignocellulose, which is composed of cellulose, hemicellulose and lignin, and has the characteristics of complex components and dense structure. Cellulose is a high-crystallinity macromolecule composed of glucose units, which is relatively difficult to hydrolyze; hemicellulose is an amorphous heteropolymer composed of monosaccharides such as xylose, arabinose, and mannose, which is easy to degrade under acidic conditions; and lignin is a highly cross-linked three-dimensional aromatic polymer composed of three aromatic monomers: coumarin, coniferyl alcohol, and sinapyl alcohol. Due to the large differences in the constituent units and chemical properties of the three components of biomass, the conversion process conditions of each component are significantly different, and it is difficult to achieve the selective conversion of the three components at the same time under a single condition. Therefore, breaking the connection of the three components in advance through pretreatment technology is a prerequisite for realizing the utilization of all components of biomass. However, traditional pretreatment technology usually needs to be carried out under harsh conditions such as the participation of strong acids, strong bases, strong oxidants, etc. or high temperatures, resulting in the breakage of ether bonds with relatively low dissociation energy in lignin and the formation of stable CC bonds, which affects the subsequent efficient depolymerization and utilization of biomass.
[0010] In the lignocellulose of biomass, cellulose serves as the skeleton structure of the cell wall, and its arrangement is regular and orderly, consisting of a large amount of crystalline and a small amount of amorphous. Hemicellulose and lignin are filled between the microfibrils through ether bonds and ester bonds, acting as an adhesive. This mutually cross-linked structure also forms a dense protective layer that wraps the surface of the cellulose microfibrils. The complex cross-linked structure of lignocellulose brings challenges to its conversion and application.
[0011] Moreover, the structural characteristics of high crystallinity and high degree of polymerization also lead to the strong hydrophobicity of cellulose. In the catalytic reaction, the dense crystal structure seriously hinders the accessibility of the catalyst to the active sites represented by glycosidic bonds, limiting the directional conversion of cellulose. Therefore, destroying the hydrogen bonds in cellulose, reducing its crystallinity, improving its solubility, and exposing more catalytic active sites are the prerequisites for achieving directional conversion of cellulose. In order to destroy the hydrogen bonds to achieve cellulose hydrolysis, the traditional pretreatment process usually requires the use of high acid and high temperature conditions, which not only easily leads to the decomposition of hydrolyzed sugars to produce more by-products, but also the lignin β-O-4 bond is easy to break under strong acid, strong alkali, and high temperature conditions, resulting in lignin being highly condensed to form a stable CC bond that is ultimately difficult to break, making it difficult to depolymerize lignocellulose and restricting its directional conversion. Therefore, the use of new pretreatment technology, under the premise of effectively retaining the β-O-4 bond in lignin, is the key to achieving high-value utilization of all components of lignocellulose, including lignin.
[0012] Therefore, according to one aspect of the present invention, the biomass is first pretreated. In order to achieve the above purpose, a method for treating biomass with an active liquid for depolymerization pretreatment is also provided, including preparing an active liquid for depolymerization pretreatment and treating biomass with the active liquid. The active liquid can promote the depolymerization of cellulose, hemicellulose and lignin in the biomass into small organic molecules, wherein the pretreatment steps of the biomass include:
[0013] S001, after drying the biomass, shearing it with a high-speed shearing machine to obtain crushed wood cellulose for later use;
[0014] The preparation of the active liquid pretreated by depolymerization comprises the following steps:
[0015] S002, in a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, an inorganic ion solution is added, and after stirring evenly, formic acid and ethylene glycol are added, and stirred evenly, and then graphene is added and dispersed evenly to obtain an active liquid pretreated by depolymerization;
[0016] S003, at a temperature of 70-80°C, the crushed lignocellulose and the active liquid of the depolymerization pretreatment are mixed in a mass ratio of 1:2-3 to obtain a solid-liquid mixture; stirring for 2-3 hours to allow the active liquid of the depolymerization pretreatment and the crushed lignocellulose particles to fully contact and react, thereby activating the lignocellulose and protecting the β-O-4 bond in the lignin, and washing with a large amount of water and filtering to obtain a biomass pretreatment product;
[0017] S004, adding deionized water in a weight ratio of 3 to 5 times that of the biomass pretreatment material, adding citric acid, and then adding β-glucanase, controlling the temperature at 30 to 40° C., stirring for 2 to 3 hours, further promoting the hydrolysis of high-crystallinity macromolecules composed of glucose units in cellulose, and obtaining a first material of oligosaccharides containing low-molecular-weight glucose units; the added β-glucanase accounts for 0.1 to 0.2 parts by weight of the biomass pretreatment material, and its enzyme activity is ≥80,000 U / g, and the citric acid is 1 to 2 parts.
[0018] Studies have found that LiBr and ZnCl2 can only dissolve and hydrolyze cellulose well when the coordination number of water is about 3, while ZnCl2·3H2O exists in the form of [Zn(OH2)6][ZnCl4] in the solution, which can dissolve and hydrolyze cellulose, but ZnCl2·2H2O or ZnCl2·4H2O cannot dissolve cellulose. This is mainly because the coordination number of the cationic hydration layer plays a decisive role in the dissolution or hydrolysis of cellulose. Zn coordinates with the primary hydroxyl group of cellulose and five water molecules to meet the six-coordination number of Zn to form the first hydration layer, while the hydroxyl group on the cellulose sugar ring forms a hydrogen bond with the strong hydrogen bond donor in the first hydration layer to form the second hydration layer, leading to the dissolution of cellulose. Studies have also found that Cl is more likely to form hydrogen bonds with the hydrogen in the hydroxyl group of cellulose than Br, but LiBr is more effective than LiCl in promoting the hydrolysis of cellulose. Therefore, in addition to hydrogen bonds, the interaction between inorganic ion solution and cellulose should also include van der Waals forces. Therefore, it is necessary to use molecular simulation to study the effects of cations and anions on cellulose hydrolysis at a microscopic level. Therefore, in order to depolymerize biomass to a greater extent, the inorganic ion solution is LiBr·3H2O, ZnCl2·3H2O and water in a mass ratio of (1-2):(3-5):10-15.
[0019] Wherein, the mass ratio of graphene, ethylene glycol, formic acid and inorganic ion solution is (0.1-0.2):1:4:10-15.
[0020] Furthermore, in order to enable biomass to produce more hydrogen, the purpose of the present invention is to provide a biomass efficient hydrogen production catalytic system, which can not only significantly improve the efficiency of hydrogen production, but also recycle the catalyst used in the biomass hydrogen production process, thereby reducing the catalytic cost of biomass hydrogen production.
[0021] In order to solve the above problems, we also provide a catalyst for depolymerization of hydrogen, a multi-metal magnetic porous catalyst loaded with iron, nickel and zirconium multi-metal elements on a material with a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin, and a method for catalytic depolymerization of biomass using the catalyst. Studies have found that the preparation of hydrogen production catalysts is developing towards metal nanoparticles with small particle sizes. The mainstream metal nanoparticle catalysts are mainly some precious metals, such as active elements such as Au, Pd, Ni and Ir, but due to the scarce reserves of precious metals, high prices and ultra-small size, and the metal nanoparticles are usually thermodynamically unstable due to their own high surface energy, agglomeration phenomenon greatly affects the practical application of the catalyst and catalytic efficiency. In order to better disperse these metal nanoparticles, dispersants are usually used, but dispersants will contaminate the surface of metal nanoparticles to a certain extent, reducing the catalytic performance. In order to solve this problem, we further found that appropriate carriers can better disperse and fix metal nanoparticles on the carrier, thereby significantly improving the catalytic performance of metal nanoparticle catalysts in the process of biomass hydrogen production. In recent years, people have found that a variety of carrier materials can carry metal nanoparticles, which can be mainly divided into metal organic frameworks, carbon materials, organic compounds, etc. Various carriers have their own unique advantages, but as dehydrogenation catalyst carriers, they all need to show high surface area, good porosity and strong interaction between the carrier and the metal nanoparticles.
[0022] Therefore, we first prepared a material with a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin, which has a high surface area and good porosity and can be used as a carrier; specifically:
[0023] S101, soaking calcium-based montmorillonite in dilute hydrochloric acid for 1-2 hours, then adding tetraethyl orthosilicate, stirring and reacting at 80-90° C. to crack the interlayer lattice of the montmorillonite and expand the interlayer distance to obtain modified montmorillonite; wherein the mass ratio of tetraethyl orthosilicate to calcium-based montmorillonite is 1:10;
[0024] S102, at room temperature, ultrasonically dispersing the modified montmorillonite into toluene 2 to 3 times the weight of the modified montmorillonite, then heating to 80 to 90° C., slowly adding (3-methylaminopropyl)trimethoxysilane under stirring, and continuing stirring for 5 to 6 hours; after the reaction is completed, cooling to room temperature, centrifuging, washing with a large amount of ethanol and water, and drying to obtain aminated montmorillonite with negatively charged NH2-groups on the surface; wherein the mass ratio of (3-methylaminopropyl)trimethoxysilane to the modified montmorillonite is 2 to 3:5;
[0025] S103, adding 5% citric acid to β-cyclodextrin and stirring evenly to make the pH value 5.5-6.5, so that the β-cyclodextrin is fully dispersed in the dilute citric acid solution, heating to 60° C., adding glutamic acid, stirring well, reacting for 1-2 hours, and obtaining a modified β-cyclodextrin suspension with a positively charged surface;
[0026] S104, dispersing the aminated montmorillonite with negatively charged NH2 groups on the surface into a modified β-cyclodextrin suspension with positive charges on the surface, slowly stirring and reacting for 2 to 3 hours, grafting β-cyclodextrin to the interlayer of the montmorillonite, centrifuging and filtering, and drying at low temperature to obtain a material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin; wherein the mass ratio of glutamic acid, β-cyclodextrin and citric acid dilute solution is 3 to 5:8 to 15:100; and the mass ratio of β-cyclodextrin to aminated montmorillonite with negatively charged NH2 groups on the surface is 1:5;
[0027] Further, a multi-metal magnetic porous catalyst is prepared, specifically
[0028] S105, mixing ferroferric oxide, iron, zirconium tetrachloride, nickel nitrate hexahydrate and 50% ethanol solution to obtain a metal system mixed solution; the mass ratio of ferroferric oxide, iron, zirconium tetrachloride and nickel nitrate hexahydrate is 4:1:(1-2):(1-2); adding the aminated montmorillonite mesh porous structure grafted with β-cyclodextrin and the metal system mixed solution into a high pressure reactor at a pressure of 0.5 MPa under nitrogen protection to react, then adding ethylenediamine, stirring evenly, and heating at 160-200°C. temperature, the reaction time is 14 to 18 hours. After the reaction is completed, it is cooled to room temperature to obtain a suspension; centrifugal separation is performed to obtain a precipitate, the precipitate is washed 5 to 6 times, calcined at a temperature of 180 to 200°C for 2 hours, and ground to obtain a final product, which is recorded as a multi-metal magnetic porous catalyst; wherein the mass concentration of the substance with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is 30%, and the total mass concentration of the four substances of ferrosoferric oxide, iron, zirconium tetrachloride and nickel nitrate hexahydrate is 8 to 12%.
[0029] The multi-metal magnetic porous catalyst uses a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin as the skeleton to form a porous framework with a large specific surface area. The iron, nickel and zirconium metal elements are loaded in the porous structure to form a stable catalyst system. Figure 1The electron microscope scanning image of the multi-metal magnetic porous catalyst also shows that there is no obvious agglomeration phenomenon, the size is small and the dispersion is relatively uniform. It can be seen that the porous structure is uniformly dispersed, and the dispersion and uniform porosity are achieved through the strong interaction between the metal elements and the carrier. This also effectively enhances the interaction between the two and increases the specific surface area, which is conducive to the dehydrogenation reaction of biomass decomposition. The material with a mesh-like porous structure of β-cyclodextrin amino montmorillonite forms a large number of microporous structures after cross-linking post-treatment, and carbon atom defects will appear at high temperatures. The more carbon atom defects mean that there are more active sites on its surface and inside, so the more points that the Fe-Ni-Zr metal elements can be loaded, and the more loading opportunities for active ingredients, so that the obtained multi-metal magnetic porous catalyst has higher activity, and thus has a better catalytic effect in the biomass decomposition hydrogen production reaction.
[0030] Finally, a method for producing hydrogen from biomass is as follows:
[0031] S201, in a sealed reactor, replacing the gas in the sealed reactor with oxygen 1 to 2 times, maintaining a pressure of 0.2 to 0.5 MPa, using a multi-metal magnetic porous catalyst as a catalytic system, a first material as a reaction substrate, and oxygen as an oxidant, depolymerizing the first material at 80 to 110° C. to obtain a second material;
[0032] S202, in a sealed reactor, replacing the gas in the sealed reactor with protective gas 2 to 3 times, and maintaining a pressure of 0.2 to 0.8 MPa, mixing the second material and the multi-metal magnetic porous catalyst, heating to 120 to 150° C. and stirring under a protective atmosphere to perform a catalytic depolymerization reaction to obtain gaseous volatiles, and the gaseous volatiles are fully contacted with the alkaline absorbent limestone in radial and axial directions to obtain hydrogen;
[0033] The protective atmosphere is nitrogen or argon; the mass ratio of the first material to the multi-metal magnetic porous catalyst is 50-60:1; the mass ratio of the second material to the multi-metal magnetic porous catalyst is 20-25:1; and the total reaction time of the catalytic depolymerization is 4-6 hours.
[0034] The aminated montmorillonite in the multi-metal magnetic porous catalyst is not only a carrier, but also promotes the release of H2 from biomass by introducing amine group functionalization. Due to the complexity of the chemical structure of lignocellulose in biomass, in addition to the CO bond, there is also a CC bond structure with relatively high dissociation energy. Therefore, efficient breaking of CO and CC bonds requires the synergistic catalysis of different active sites. The synergistic catalysis of multi-metal multifunctional groups in the multi-metal magnetic porous catalyst allows biomass to be efficiently catalyzed to obtain a high conversion rate of hydrogen while also reducing the reaction temperature and shortening the reaction time. In addition, the catalyst is easy to separate from the reaction system, and the catalytic reaction is easy to control, further improving the catalytic activity and selectivity of the metal catalyst system, so as to efficiently prepare hydrogen by decomposing biomass at low temperatures.
[0035] Compared with the prior art method of producing hydrogen from biomass by thermal catalysis, which has high reaction temperature, long reaction time and low yield, the beneficial effects of the invention are as follows:
[0036] 1. The present invention uses a multi-metal magnetic porous catalyst to realize a method for efficiently producing hydrogen from biomass hydrolyzate, which has a good catalytic cycle effect. It solves the problems of unstable catalyst structure and incompatibility between catalyst and biomass hydrolyzate in the original technology. By optimizing the catalyst structure and the porous carrier of the catalyst, the active catalytic speed of the catalyst on biomass is improved, and an efficient hydrogen production process using biomass hydrolyzate and catalyst is realized. Compared with the original technology, the preparation of the catalyst involved in this technology is simpler and more efficient, and the catalyst can be recycled and reused, which is of great significance to the industrial application of this technology.
[0037] 2. The present invention provides a method for pretreating biomass, by preparing an active liquid for depolymerization pretreatment, pretreating the biomass, so that the active liquid for depolymerization pretreatment and the crushed cellulose particles are fully in contact and reacted, thereby activating the cellulose and protecting the β-O-4 bonds in the lignin, so that in the subsequent aggregation and hydrogen production process, the biomass is more easily depolymerized into small organic molecules, effectively improving the composition of the biomass hydrolyzate, with low by-products and a conversion efficiency of more than 85%.
[0038] 3. The present invention also provides a method for preparing a multi-metal magnetic porous catalyst loaded with iron, nickel and zirconium multi-metal elements from a material having a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin. The material having a mesh-like porous structure of aminated montmorillonite of β-cyclodextrin forms a large number of microporous structures through a cross-linking post-treatment process, and has many active sites on the surface and inside, so that the obtained multi-metal magnetic porous catalyst has high activity and obtains high-quality hydrogen products; the high-quality hydrogen concentration can reach up to 96%, the carbon dioxide content is less than 3%, other impurity gases do not exceed 0.5%, and the hydrogen production is not less than 160g hydrogen / kg biomass. The catalyst is also magnetic, easy to recycle, and can be repeatedly catalyzed.
[0039] 4. The biomass hydrogen production method of the present invention has the advantages of simple process, high hydrogen yield and high energy utilization rate. The raw materials are easily available and renewable; the reaction conditions are mild and the energy consumption is low; the waste biomass is efficiently developed and utilized, which helps to solve the energy crisis and environmental pollution problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 , SEM scanning image of the multi-metallic magnetic porous catalyst prepared in Example 1. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] Example 1
[0043] A method for producing hydrogen from biomass, firstly providing a depolymerization pre-treated active liquid to treat the biomass, the pre-treatment steps of the biomass comprising:
[0044] Firstly, the corn stalks are dried and then shredded with a high-speed shearing machine to obtain crushed wood cellulose for later use;
[0045] In a reaction kettle equipped with a stirring blade, a thermometer, and a condenser, 1 part of LiBr·3H2O, 3 parts of ZnCl2·3H2O, and 10 parts of water were added and stirred evenly, and then 4 parts of formic acid and 1 part of ethylene glycol were added and stirred evenly, and then 0.1 parts of graphene were added and dispersed evenly to obtain a depolymerization pretreated active liquid;
[0046] The temperature was raised to 70°C, 10 parts of crushed lignocellulose were mixed with 30 parts of depolymerization pretreatment active liquid to obtain a solid-liquid mixture; the mixture was stirred for 3 hours to allow the depolymerization pretreatment active liquid and crushed lignocellulose particles to fully contact and react, thereby activating the lignocellulose and protecting the β-O-4 bond in the lignin; a biomass pretreatment product was obtained after washing with a large amount of water and filtering;
[0047] Take 10 parts of biomass pretreatment material, add 30 parts of deionized water, add 1 part of citric acid, and then add 1 part of β-glucanase, whose enzyme activity is ≥ 80,000 U / g, control the temperature at 35°C and stir for 3 hours to further promote the hydrolysis of high-crystallinity macromolecules composed of glucose units in cellulose, and obtain a first material of oligosaccharides containing low molecular weight glucose units;
[0048] Furthermore, a material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is prepared. Specifically:
[0049] 10 parts of calcium-based montmorillonite were soaked in dilute hydrochloric acid for 1 hour, and then 1 part of ethyl orthosilicate was added, and stirred at 80°C to react so that the interlayer lattice of the montmorillonite was cracked and the interlayer distance was expanded to obtain modified montmorillonite;
[0050] At room temperature, 10 parts of modified montmorillonite were ultrasonically dispersed in 30 parts of toluene, then heated to 80°C, and 4 parts of (3-methylaminopropyl)trimethoxysilane were slowly added under stirring, and stirring was continued for 5 hours. After the reaction was completed, it was cooled to room temperature, centrifuged, washed with a large amount of ethanol and water, and dried to obtain aminated montmorillonite with negatively charged NH2- groups on the surface.
[0051] 8 parts of β-cyclodextrin were added to 100 parts of 5% citric acid and stirred evenly, the pH value was 5.8, and the β-cyclodextrin was fully dispersed in the dilute citric acid solution, the temperature was raised to 60°C, 3 parts of glutamic acid were added, stirred well, and reacted for 2 hours to obtain a modified β-cyclodextrin suspension with a positive charge on the surface;
[0052] 40 parts of aminated montmorillonite with negatively charged NH2 groups on the surface are dispersed in a modified β-cyclodextrin suspension with positively charged surface, and the reaction is slowly stirred for 3 hours. The β-cyclodextrin is grafted to the interlayer of the montmorillonite. After centrifugal filtration and low-temperature drying, a material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is obtained.
[0053] Furthermore, a multi-metal magnetic porous catalyst is prepared, specifically:
[0054] 4 parts of ferrosoferric oxide, 1 part of iron, 2 parts of zirconium tetrachloride, 3 parts of nickel nitrate hexahydrate and 50% ethanol solution are stirred and mixed to obtain a metal system mixed solution; 30 parts of a substance with a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin and the metal system mixed solution are added together into a high-pressure reactor at a pressure of 0.5 MPa under nitrogen protection for reaction, and then 2 parts of ethylenediamine are added and stirred evenly, and the reaction is carried out at a temperature of 160° C. for 14 hours. After the reaction is completed, the suspension is cooled to room temperature to obtain a suspension; centrifugal separation is performed to obtain a precipitate, the precipitate is washed 5 to 6 times, calcined at a temperature of 200° C. for 2 hours, and ground to obtain a multi-metal magnetic porous catalyst;
[0055] Finally, a method for producing hydrogen from biomass is as follows:
[0056] In a sealed reactor, the gas in the sealed reactor is replaced once with oxygen and the pressure is maintained at 0.5 MPa. One more part of the metal magnetic porous catalyst is used as the catalytic system, 60 parts of the first material is used as the reaction substrate, and oxygen is used as the oxidant. The first material is further depolymerized at 110° C. for 2 hours to obtain the second material.
[0057] In a closed reactor, the gas in the sealed reactor was replaced with protective gas for 3 times, and the pressure was maintained at 0.2 MPa. 50 parts of the second material and 2 parts of the multi-metal magnetic porous catalyst were mixed, and the temperature was raised to 120°C and stirred for catalytic depolymerization under nitrogen protection. The reaction lasted for 3 hours to obtain gaseous volatiles, which were fully contacted with the alkaline absorbent limestone in radial and axial directions to obtain hydrogen. The obtained gas was quantified by GC, and the hydrogen concentration reached 96.3%, the carbon dioxide content was 2.3%, and other impurity gases were 1.4%.
[0058] Example 2
[0059] A method for producing hydrogen from biomass, firstly providing a depolymerization pre-treated active liquid to treat the biomass, the pre-treatment steps of the biomass comprising:
[0060] Firstly, the wheat straw is dried and then shredded with a high-speed shearing machine to obtain crushed wood cellulose for later use;
[0061] In a reaction kettle equipped with a stirring blade, a thermometer, and a condenser, 2 parts of LiBr·3H2O, 5 parts of ZnCl2·3H2O, and 15 parts of water were added and stirred evenly, and then 8 parts of formic acid and 2 parts of ethylene glycol were added and stirred evenly, and then 0.4 parts of graphene was added and dispersed evenly to obtain a depolymerization pretreated active liquid;
[0062] The temperature is raised to 70°C, 10 parts of crushed lignocellulose are mixed with 20 parts of depolymerization pretreatment active liquid to obtain a solid-liquid mixture; the mixture is stirred for 2 hours to allow the depolymerization pretreatment active liquid and crushed lignocellulose particles to fully contact and react, thereby activating the lignocellulose and protecting the β-O-4 bond in the lignin; a biomass pretreatment product is obtained after washing with a large amount of water and filtering;
[0063] Take 10 parts of biomass pretreatment material, add 50 parts of deionized water, add 2 parts of citric acid, and then add 1 part of β-glucanase, whose enzyme activity is ≥ 80,000 U / g, control the temperature at 37°C and stir for 2 hours to further promote the hydrolysis of high-crystallinity macromolecules composed of glucose units in cellulose, and obtain a first material of oligosaccharides containing low molecular weight glucose units;
[0064] Further, a material having a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is prepared, specifically:
[0065] 10 parts of calcium-based montmorillonite were soaked in dilute hydrochloric acid for 1 hour, and then 1 part of ethyl orthosilicate was added, and stirred at 80°C to react so that the interlayer lattice of the montmorillonite was cracked and the interlayer distance was expanded to obtain modified montmorillonite;
[0066] At room temperature, 10 parts of modified montmorillonite were ultrasonically dispersed in 30 parts of toluene, then heated to 80°C, and 6 parts of (3-methylaminopropyl)trimethoxysilane were slowly added under stirring, and stirring was continued for 5 hours. After the reaction was completed, it was cooled to room temperature, centrifuged, and washed with a large amount of ethanol and water. After drying, an aminated montmorillonite with negatively charged NH2- groups on the surface was obtained. The mass ratio of (3-methylaminopropyl)trimethoxysilane to modified montmorillonite was 2 to 3:5;
[0067] 15 parts of β-cyclodextrin were added to 100 parts of 5% citric acid and stirred evenly, the pH value was 6.1, and the β-cyclodextrin was fully dispersed in the dilute citric acid solution, the temperature was raised to 60°C, 5 parts of glutamic acid were added, stirred well, and reacted for 2 hours to obtain a modified β-cyclodextrin suspension with a positive charge on the surface;
[0068] 75 parts of aminated montmorillonite with negatively charged NH2 groups on the surface are dispersed in a modified β-cyclodextrin suspension with positive charge on the surface, and the reaction is slowly stirred for 3 hours, β-cyclodextrin is grafted to the interlayer of montmorillonite, centrifuged and filtered, and low-temperature dried to obtain a material with a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin. Further, a multi-metal magnetic porous catalyst is prepared, specifically
[0069] 4 parts of ferrosoferric oxide, 1 part of iron, 2 parts of zirconium tetrachloride, 1 part of nickel nitrate hexahydrate and 50% ethanol solution are stirred and mixed to obtain a metal system mixed solution; 30 parts of a substance with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin and the metal system mixed solution are added together into a high-pressure reactor at a pressure of 0.5 MPa under nitrogen protection for reaction, and then 2 parts of ethylenediamine are added and stirred evenly. The reaction time is 14 hours at a temperature of 160°C. After the reaction is completed, the mixture is cooled to room temperature to obtain a suspension; centrifugal separation is performed to obtain a precipitate, the precipitate is washed 5 to 6 times, calcined at a temperature of 200°C for 2 hours, and ground to obtain a multi-metal magnetic porous catalyst.
[0070] Finally, a method for producing hydrogen from biomass is as follows:
[0071] In a sealed reactor, the gas in the sealed reactor is replaced once with oxygen and the pressure is maintained at 0.5 MPa. One more part of the metal magnetic porous catalyst is used as the catalytic system, 50 parts of the first material is used as the reaction substrate, and oxygen is used as the oxidant. The first material is further depolymerized at 80° C. for 2 hours to obtain the second material.
[0072] In a closed reactor, the gas in the sealed reactor was replaced with protective gas for 3 times, and the pressure was maintained at 0.5 MPa. After 40 parts of the second material and 2 parts of the multi-metal magnetic porous catalyst were mixed, the temperature was raised to 130°C and stirred for catalytic depolymerization under nitrogen protection, and the reaction was carried out for 3 hours to obtain gaseous volatiles, which were fully contacted with the alkaline absorbent limestone in radial and axial directions to obtain hydrogen. The reaction gas was quantified by GC, and the hydrogen concentration reached 97.1%, the carbon dioxide content was 1.6%, and other impurity gases were 1.3%.
[0073] Example 3
[0074] A method for producing hydrogen from biomass, firstly providing a depolymerization pre-treated active liquid to treat the biomass, the pre-treatment steps of the biomass comprising:
[0075] Firstly, the rice straw is dried and then shredded with a high-speed shearing machine to obtain crushed wood cellulose for later use;
[0076] In a reaction kettle equipped with a stirring blade, a thermometer, and a condenser, 2 parts of LiBr·3H2O, 4 parts of ZnCl2·3H2O, and 14 parts of water were added and stirred evenly, and then 4 parts of formic acid and 1 part of ethylene glycol were added and stirred evenly, and then 0.15 parts of graphene were added and dispersed evenly to obtain a depolymerization pretreated active liquid;
[0077] The temperature is raised to 70°C, 10 parts of crushed lignocellulose are mixed with 20 parts of depolymerization pretreatment active liquid to obtain a solid-liquid mixture; the mixture is stirred for 2 hours to allow the depolymerization pretreatment active liquid and crushed lignocellulose particles to fully contact and react, thereby activating the lignocellulose and protecting the β-O-4 bond in the lignin; a biomass pretreatment product is obtained after washing with a large amount of water and filtering;
[0078] Take 10 parts of biomass pretreatment material, add 40 parts of deionized water, add 2 parts of citric acid, and then add 1 part of β-glucanase, whose enzyme activity is ≥ 80,000 U / g, control the temperature at 35°C and stir for 3 hours to further promote the hydrolysis of high-crystallinity macromolecules composed of glucose units in cellulose, and obtain the first material of oligosaccharides containing low molecular weight glucose units;
[0079] Furthermore, a material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is prepared. Specifically:
[0080] 10 parts of calcium-based montmorillonite were soaked in dilute hydrochloric acid for 1 hour, and then 1 part of ethyl orthosilicate was added, and stirred at 80°C to react so that the interlayer lattice of the montmorillonite was cracked and the interlayer distance was expanded to obtain modified montmorillonite;
[0081] At room temperature, 10 parts of modified montmorillonite were ultrasonically dispersed in 20 parts of toluene, then heated to 80°C, and 5 parts of (3-methylaminopropyl)trimethoxysilane were slowly added under stirring, and stirring was continued for 5 hours. After the reaction was completed, it was cooled to room temperature, centrifuged, washed with a large amount of ethanol and water, and dried to obtain aminated montmorillonite with negatively charged NH2- groups on the surface.
[0082] 12 parts of β-cyclodextrin were added to 100 parts of 5% citric acid and stirred evenly, the pH value was 5.8, and the β-cyclodextrin was fully dispersed in the dilute citric acid solution, the temperature was raised to 60°C, 4 parts of glutamic acid were added, stirred well, and reacted for 2 hours to obtain a modified β-cyclodextrin suspension with a positive charge on the surface;
[0083] 60 parts of aminated montmorillonite with negatively charged NH2 groups on the surface are dispersed in a modified β-cyclodextrin suspension with positively charged surface, and the mixture is slowly stirred for reaction for 3 hours. The β-cyclodextrin is grafted between the layers of the montmorillonite. The mixture is centrifugally filtered and dried at low temperature to obtain a material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin.
[0084] Furthermore, a multi-metal magnetic porous catalyst is prepared, specifically:
[0085] 4 parts of ferrosoferric oxide, 1 part of iron, 2 parts of zirconium tetrachloride, 2 parts of nickel nitrate hexahydrate and 50% ethanol solution are stirred and mixed to obtain a metal system mixed solution; 30 parts of a substance with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin and the metal system mixed solution are added together into a high-pressure reactor at a pressure of 0.5 MPa under nitrogen protection for reaction, and then 2 parts of ethylenediamine are added and stirred evenly. The reaction is carried out at a temperature of 160°C for 14 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a suspension; centrifugal separation is performed to obtain a precipitate, the precipitate is washed 5 to 6 times, calcined at a temperature of 180°C for 2 hours, and ground to obtain a multi-metal magnetic porous catalyst.
[0086] Finally, a method for producing hydrogen from biomass is as follows:
[0087] In a sealed reactor, the gas in the sealed reactor is replaced once with oxygen, and the pressure is maintained at 0.3 MPa. One more part of the metal magnetic porous catalyst is used as the catalytic system, 60 parts of the first material is used as the reaction substrate, and oxygen is used as the oxidant. The first material is further depolymerized at 110° C. and reacted for 3 hours to obtain the second material.
[0088] In a closed reactor, the gas in the sealed reactor was replaced with protective gas for 3 times, and the pressure was maintained at 0.5 MPa. 50 parts of the second material and 2 parts of the multi-metal magnetic porous catalyst were mixed, and the temperature was raised to 150°C and stirred for catalytic depolymerization under nitrogen protection. The reaction lasted for 2 hours to obtain gaseous volatiles, which were fully contacted with the alkaline absorbent limestone in radial and axial directions to obtain hydrogen. The obtained gas was quantified by GC, and the hydrogen concentration reached 96.8%, the carbon dioxide content was 1.9%, and other impurity gases were 1.3%.
[0089] Comparative Example 1: The biomass was pretreated with an equal amount of common 10% concentrated sulfuric acid instead of the active liquid in the depolymerization pretreatment, and the rest was the same as in Example 1;
[0090] Comparative Example 2, when preparing the catalyst, an equal amount of activated carbon was used instead of the substance with a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin as a carrier, and the obtained catalyst replaced the substance with an equal amount of aminated montmorillonite mesh-like porous structure grafted with β-cyclodextrin to load a multi-metal magnetic porous catalyst of iron, nickel and zirconium multi-metal elements, and the rest was the same as in Example 1;
[0091] In comparative example 3, the biomass is pretreated with an equal amount of common 10% concentrated sulfuric acid instead of the active liquid of the depolymerization pretreatment, and when preparing the catalyst, an equal amount of activated carbon is used instead of the substance with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin as a carrier, and the obtained catalyst replaces the substance with an equal amount of the grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin. The rest is the same as in example 1;
[0092] In comparative example 4, the biochar-based Fe-Ni-Ca catalyst prepared in the third step of Example 1 in the preparation method of a biochar-based bifunctional catalyst with publication number CN115254126B was used to replace the catalyst in equal amount, and the rest was the same as in Example 1.
[0093] Experimental effect comparison data
[0094] 1. Measure the content of β-O-4 bonds in the first material
[0095] The first material in Examples 1-3 and Comparative Examples 1-3 was treated with a magnetic resonance spectrometer to obtain a two-dimensional nuclear magnetic resonance carbon-hydrogen spectrum, analyze the hydrogen spectrum, and measure and analyze the β-O-4 bonds in the reaction-obtained material, and the data were recorded as shown in Table 1; As can be seen from Table 1, Examples 1-3 and Comparative Example 2 are the first materials obtained by treating the lignocellulose in the biomass with the active liquid pre-treated by depolymerization, and at this time, most of the β-O-4 bonds in the first material are properly protected and not broken, so that the subsequent biomass degradation selectivity is high and the conversion rate of degradation into small molecule organic matter is high. However, in Comparative Examples 1 and 3, most of the β-O-4 bonds in the first material obtained by the traditional acid treatment method are broken, and only a small amount of β-O-4 bonds are not destroyed, which makes it very difficult for the first material to be subsequently degraded into small molecule organic matter, thereby reducing the hydrogen conversion rate.
[0096] Table 1, β-O-4 bond content measurement data record in the first material
[0097] Sample name β-O-4 bond (%) Example 1 45.86 Example 2 47.19 Example 3 46.98 Comparative Example 1 8.39 Comparative Example 2 44.91 Comparative Example 3 7.79
[0098] 2. Measure the composition analysis of biomass depolymerization products in the second material
[0099] High performance liquid chromatography was used, with a chromatographic column: Agilent ZORBAXSB-C18 column (5 μm×4.6 mm×250 mm), a mobile phase of methanol: KH2PO4 buffer solution (20 mmol / L, pH 2.6) = 5:95, a detection wavelength of 197 nm, a column temperature of 25°C, an injection volume of 20 μL, and a flow rate of 0.8 mL / min. The components of the organic small molecules in the second material in Examples 1-3 and Comparative Examples 1-4 were qualitatively and quantitatively analyzed, and the test results are shown in Table 2. As can be seen from Table 2, because Examples 1-3 and 4 are firstly treated with the active liquid of the depolymerization pretreatment to obtain the first material, at this time, most of the β-O-4 bonds in the first material are properly protected, and therefore, the first material is depolymerized with the multi-metal magnetic porous catalyst loaded with iron-nickel-zirconium multi-metal elements of the material with the aminated montmorillonite grid-like porous structure grafted with β-cyclodextrin, so that the depolymerization product selectivity is high, and most of the components in the first material are selectively degraded into small organic molecules, and more than 89% of the small organic molecules are degraded into formic acid, and the rest are degraded into small molecules of glucose, and the conversion rate of formic acid and small molecules of glucose into hydrogen in further catalytic reactions is very high. Although Comparative Examples 2 and 4 are also firstly treated with the active liquid of the depolymerization pretreatment to obtain the first material, at this time, most of the β-O-4 bonds in the first material are also properly protected, but because the catalyst used in the depolymerization process is selected or low in activity due to high temperature, it is easy to agglomerate, resulting in a low conversion rate of small organic molecules such as formic acid and glucose. In Comparative Example 1, because the pretreatment has caused the lignocellulose in the biomass to condense into difficult-to-degrade substances, the subsequent catalytic degradation efficiency is very low, and only 34% of the lignocellulose is converted into small molecular organic matter, which seriously restricts the depolymerization conversion rate of the biomass.
[0100] Table 2 Composition analysis of biomass depolymerization products in the second material
[0101]
[0102]
[0103] 3. Characterization of the performance of multi-metallic magnetic porous catalysts
[0104] In a JW-BK200C specific surface area and pore size analyzer, the catalyst was first vacuum degassed at 200°C for 8 hours, and then the catalyst samples in Examples 1-3 and Comparative Examples 1-4 were tested at liquid nitrogen temperature to obtain the specific surface area (m 2 / g) and porosity (%), as shown in Table 3. From this, it can be seen that the catalysts involved in Examples 1-3 have larger specific surface area and porosity, and have a more significant promoting effect on the forward progress of the catalytic reaction.
[0105] Table 3 Performance characterization data of multi-metallic magnetic porous catalysts
[0106] Sample name <![CDATA[Specific surface area (m 2 / g)]]> Porosity (%) Example 1 243.18 25.9 Example 2 260.64 28.2 Example 3 251.73 26.5 Comparative Example 1 231.61 24.2 Comparative Example 2 24.27 12.6 Comparative Example 3 23.82 11.3 Comparative Example 4 93.94 18.9
[0107] The morphology of the samples was observed using a field emission scanning electron microscope of the FEI Nova NanoSEM450 type. Before the test, the catalyst sample in Example 1 was evenly dispersed on the conductive glue, and the parameters of the scanning electron microscope were adjusted to set the acceleration voltage to 5-10 kV, the detection current to 10 mA, the resolution to 1.7 nm, and the magnification to 1000 times; the morphology is shown in Figure 1 .Depend on Figure 1 It can be seen that the catalyst in Example 1 self-assembles in an orderly manner to form a material with a grid-like porous structure. The material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is used as a skeleton to form a porous framework, and the iron, nickel and zirconium metal elements are loaded in the porous structure. Figure 1 It can also be seen from the electron microscope scanning that there is no agglomeration phenomenon, the size is small and the dispersion is relatively uniform, and the uniformly dispersed porous structure can be seen. The dispersion and uniform porosity are achieved through the strong interaction between the metal elements and the carrier. This also effectively enhances the interaction between the two and increases the specific surface area. Therefore, the catalyst has a three-dimensional porous structure, and the pore wall is composed of a large number of nanodendrites. This special morphology has a high specific surface area and a large number of active sites, such as steps, corners, knots and edges. Coupled with the electronic effect between multiple metals, the catalyst has high catalytic activity. The catalyst has high activity in the catalytic decomposition of formic acid and small molecule glucose under low temperature conditions.
[0108] 4. Measure the final gaseous substance for component analysis
[0109] The analytical instrument used was a GC-950 gas chromatograph, the carrier gas used was Ar, the flow rate was 40 mL / min, the pressure before and after the column was 0.3 MPa, TCD detection, the initial temperature, the vaporization temperature was 60°C, the thermal conductivity temperature was 70°C, and the current was 60 mA. The instrument was adjusted according to the above gas chromatography conditions, and after the baseline was stable, 0.5 mL of standard gas was injected, and the gas chromatogram of the standard gas was measured. The chromatogram of the standard sample was used for qualitative analysis, and the normalized peak area was used for quantitative analysis to obtain the hydrogen purity of Examples 1-3 and Comparative Examples 1-4, and the biomass hydrogen production rate of the entire process was analyzed, as shown in Table 4. At present, the yield of hydrogen production from biomass is low and the catalyst selectivity is poor, but the use of the catalyst prepared by us can significantly improve the hydrogen production rate. It can be seen from Table 4 that the hydrogen purity of Examples 1-3 is at least 96%, and the hydrogen production per kilogram of biomass is also 160g or more, indicating that the method of producing hydrogen from biomass of the invention not only has high hydrogen purity, high conversion rate of biomass to hydrogen, but also requires a low temperature for the preparation reaction, and consumes low energy, providing a new method for efficient utilization of biomass in the future. From the data of Comparative Examples 1-3, we can find that even if the biomass is pretreated in the same way in Comparative Example 2, due to the selectivity and activity of the catalyst, the conversion rate of hydrogen is also very low, and many by-products are obtained, so the purity of hydrogen is also low. It can be seen from this that after the biomass is pretreated, it is catalytically depolymerized by the multi-metal magnetic porous catalyst loaded with iron, nickel, and zirconium multi-metal elements of the material with a mesh-like porous structure of aminated montmorillonite grafted with β-cyclodextrin synthesized by us, so as to further improve the purity and conversion rate of hydrogen. The catalyst used in Comparative Example 4 also has the problem of low selectivity for degradation of lignocellulose in biomass and a large number of by-products, resulting in low purity of the obtained hydrogen and low conversion rate.
[0110] Table 4 Data record of hydrogen purity and hydrogen production rate obtained in the embodiments and comparative examples
[0111] Sample name Hydrogen content (%) Carbon dioxide content (%) Hydrogen production rate (g hydrogen / kg biomass) Example 1 96.3 2.3 171.4 Example 2 97.1 1.6 179.8 Example 3 96.8 1.9 166.2 Comparative Example 1 29.7 37.2 17.9 Comparative Example 2 41.8 47.5 34.8 Comparative Example 3 25.3 38.1 15.4 Comparative Example 4 68.1 23.7 79.5
[0112] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Any equal modifications and changes made to the technical solution of the present invention by ordinary persons in the art, as long as they do not deviate from the overall concept of the present invention, are still within the scope of the present invention.
Claims
1. A method for producing hydrogen from biomass, characterized in that: The method for producing hydrogen from biomass includes pre-treating biomass to obtain a first material of oligosaccharides containing low molecular weight glucose units, and also includes preparing a multi-metal magnetic porous catalyst loaded with iron-nickel-zirconium multi-metal elements on a material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin, and using the catalyst to catalyze the depolymerization of biomass to produce hydrogen; specifically, the method includes: S201, in a sealed reactor, replacing the gas in the sealed reactor with oxygen 1 to 2 times, maintaining a pressure of 0.2 to 0.5 MPa, using a multi-metal magnetic porous catalyst as a catalytic system, a first material as a reaction substrate, and oxygen as an oxidant, depolymerizing the first material at 80 to 110° C. to obtain a second material; S202, in a closed reactor, replacing the gas in the sealed reactor with protective gas 2 to 3 times, and maintaining a pressure of 0.2 to 0.8 MPa, mixing the second material and the multi-metal magnetic porous catalyst, heating to 120 to 150° C. and stirring under a protective atmosphere to perform a catalytic depolymerization reaction to obtain gaseous volatiles, and the gaseous volatiles are fully contacted with the alkaline absorbent limestone in radial and axial directions to obtain hydrogen; The biomass pretreatment includes preparing an active liquid for depolymerization pretreatment and treating the biomass with the active liquid, which specifically includes the following steps: S001, after drying the biomass, shearing it with a high-speed shearing machine to obtain crushed wood cellulose for later use; S002, in a reaction kettle equipped with a stirring paddle, a thermometer, and a condenser, an inorganic ion solution is added, and after stirring evenly, formic acid and ethylene glycol are added, and stirred evenly, and then graphene is added and dispersed evenly to obtain an active liquid pretreated by depolymerization; The inorganic ion solution is a mixture of LiBr·3H2O, ZnCl2·3H2O and water; S003, at a temperature of 70-80°C, mixing the crushed lignocellulose and the active liquid of the depolymerization pretreatment in a mass ratio of 1:2-3 to obtain a solid-liquid mixture; stirring for 2-3 hours to allow the active liquid of the depolymerization pretreatment and the crushed lignocellulose particles to fully contact and react to activate the lignocellulose, and washing with a large amount of water and filtering to obtain a biomass pretreatment product; S004, adding deionized water in a weight ratio of 3 to 5 times that of the biomass pretreatment material, adding citric acid, and then adding β-glucanase, controlling the temperature at 30 to 40°C, stirring for 2 to 3 hours, further promoting the hydrolysis of high-crystallinity macromolecules composed of glucose units in cellulose, and obtaining a first material of oligosaccharides containing low molecular weight glucose units, wherein the added β-glucanase accounts for 0.1 to 0.2 parts by weight of the biomass pretreatment material, and its enzyme activity is ≥80,000 U / g, and the citric acid is 1 to 2 parts.
2. The method for producing hydrogen from biomass according to claim 1, characterized in that: The multi-metal magnetic porous catalyst is specifically The following steps are involved: Among them, firstly, a substance with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is prepared, specifically: S101, soaking calcium-based montmorillonite in dilute hydrochloric acid for 1 to 2 hours, then adding tetraethyl orthosilicate, stirring and reacting at 80 to 90° C. to crack the interlayer lattice of the montmorillonite and expand the interlayer distance to obtain modified montmorillonite, wherein the mass ratio of tetraethyl orthosilicate to calcium-based montmorillonite is 1:10; S102, at room temperature, the modified montmorillonite is ultrasonically dispersed in toluene 2 to 3 times the weight of the modified montmorillonite, then the temperature is raised to 80 to 90°C, (3-methylaminopropyl)trimethoxysilane is slowly added under stirring, and stirring is continued for 5 to 6 hours; after the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed with a large amount of ethanol and water, and dried to obtain a NH2 - The aminated montmorillonite is prepared from aminated montmorillonite of a group; wherein the mass ratio of (3-methylaminopropyl)trimethoxysilane to the modified montmorillonite is 2 to 3:5; S103, adding β-cyclodextrin to a 5% citric acid solution and stirring evenly to make the pH value 5.5-6.5, so that the β-cyclodextrin is fully dispersed in the dilute citric acid solution, heating to 60° C., adding glutamic acid, stirring well, reacting for 1-2 hours, and obtaining a modified β-cyclodextrin suspension with a positively charged surface; S104, dispersing the aminated montmorillonite with negatively charged NH2 groups on the surface into a modified β-cyclodextrin suspension with positive charges on the surface, slowly stirring and reacting for 2 to 3 hours, grafting β-cyclodextrin to the interlayer of the montmorillonite, centrifuging and filtering, and drying at low temperature to obtain a material with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin; wherein the mass ratio of glutamic acid, β-cyclodextrin and citric acid dilute solution is 3 to 5:8 to 15:100; and the mass ratio of β-cyclodextrin to aminated montmorillonite with negatively charged NH2 groups on the surface is 1:5; Preparation of multi-metal magnetic porous catalyst, specifically S105, ferroferric oxide, iron, zirconium tetrachloride, nickel nitrate hexahydrate and 50% ethanol solution are stirred and mixed to obtain a metal system mixed solution; the mass ratio of ferroferric oxide, iron, zirconium tetrachloride and nickel nitrate hexahydrate is 4:1:(1-2):(1-3); the aminated montmorillonite grid-like porous structure grafted with β-cyclodextrin and the metal system mixed solution are added together into a high-pressure reactor at a pressure of 0.5 MPa under nitrogen protection for reaction, and then ethylenediamine is added and stirred evenly, and the mixture is heated at 160-200°C. The reaction time is 14 to 18 hours at 200 ° C. After the reaction is completed, the mixture is cooled to room temperature to obtain a suspension; the mixture is centrifuged to obtain a precipitate, the precipitate is washed 5 to 6 times, calcined at 180 to 200 ° C for 2 hours, and ground to obtain a final product, which is recorded as a multi-metal magnetic porous catalyst; wherein the mass percentage of the substance with a grid-like porous structure of aminated montmorillonite grafted with β-cyclodextrin is 30%, and the total mass percentage of ferrosoferric oxide, iron, zirconium tetrachloride and nickel nitrate hexahydrate is 8 to 12%.
3. The method for producing hydrogen from biomass according to claim 1, characterized in that: The biomass raw material is one of corn straw, wheat straw, rice straw or wood chips.
4. The method for producing hydrogen from biomass according to claim 1, characterized in that: The protective atmosphere is nitrogen or argon; the mass ratio of the first material to the multi-metal magnetic porous catalyst is 50-60:1; the mass ratio of the second material to the multi-metal magnetic porous catalyst is 20-25:1; and the total reaction time of the catalytic depolymerization is 4-6 hours.
5. The method for producing hydrogen from biomass according to claim 1, characterized in that: The inorganic ion solution is a LiBr·3H2O, ZnCl2·3H2O and water in a mass ratio of (1-2): (3-5): 10-15; the mass ratio of graphene, ethylene glycol, formic acid and the inorganic ion solution is (0.1-0.2): 1: 4: 10-15.
Citation Information
Patent Citations
A method and apparatus for efficiently producing hydrogen-rich gas from biomass
CN105692551B
A method for preparing a biochar-based bifunctional catalyst
CN115254126B
Method and system for preparing hydrogen from biomass
CN116064169A
Catalytic formation of carbon monoxide (CO) and hydrogen (H2) from biomass
CN105793192A
Method and system for preparing synthesis gas from biomass
CN116064167A